Direction and Speed Control of DC Motor Using Raspberry PI and Python-Based GUI - Kolya, Anup Kumar; Mondal, Debasish; Ghosh, Alokesh; Basu, Subhashree (International journal of hyperconnectivity and the internet of things, 2021)
This paper presents the design and implementation of control strategy for both the speed and direction of a direct current (DC) motor using Android-based application in smart phone. The Raspberry Pi 3 with a motor driver controller has been used to implement the control action via Python-based user-defined programming. The Android application has been developed using Android Developer Tools (ADT) in Java platform. The Android apps work like a client and communicates with Raspberry Pi through wi-fi connectivity. Finally, a small graphical user interface (GUI) has been created in Python in order to interface and control the motor with buttons in GUI. The advantages of GUI are that it is attractive, user friendly, and even a layman can work with the application developed in GUI.